Performance of participatory forest management in Ethiopia: institutional arrangement versus local practices. Issue 1 (2nd January 2017) - Ayana, Alemayehu N.; Vandenabeele, Nathalie; Arts, Bas
Abstract : The field of community-based natural resource management has been receiving growing scientific attention over the past two decades. Most studies, however, focus on investigating institutional designs and outcomes and pay scant attention to how community-based natural resource management arrangements are carried out in practice. Through an in-depth ethnographic case study in one of the pioneer participatory forest management (PFM) arrangements in southwest Ethiopia, this article demonstrates a significant disparity between the PFM institutional principles and actual local forest management practices. Our study confirms the usefulness of a practice-based approach to understand and explain how a newly introduced institutional arrangement is acted upon by local actors situated in their social, political and historical context. Our findings also contribute to empirical knowledge useful to instigate dialog and to critically reflect on whether and what kind of intervention is actually needed to positively influence forest management practices on the ground.